The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/chem.200500203
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Deposition onto Self‐Assembled Monolayers: New Insights into Micro‐ and Nanofabrication

Abstract: Pattern transfer with high resolution is a frontier topic in the emerging field of nanotechnologies. Electrochemical molding is a possible route for nanopatterning metal, alloys and oxide surfaces with high resolution in a simple and inexpensive way. This method involves electrodeposition onto a conducting master covered by a self-assembled alkanethiolate monolayer (SAMs). This molecular film enables direct surface-relief pattern transfer from the conducting master to the inner face of the electrodeposit, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 56 publications
2
35
0
Order By: Relevance
“…While for thiol-SAMs such as 4-mercaptopyridine the cathodic desorption in 0.1 m H 2 SO 4 is beyond the onset of hydrogen evolution and hence, can only be seen for higher pH, [23][24][25] the corresponding process for DCB-SAMs peaks around À0.3 V vs SCE, that is, just before the hydrogen evolution reaction on gold. This is a clear indication for a lower bond strength between DCB and gold as compared to thiol-SAMs on gold.…”
Section: à2mentioning
confidence: 95%
“…While for thiol-SAMs such as 4-mercaptopyridine the cathodic desorption in 0.1 m H 2 SO 4 is beyond the onset of hydrogen evolution and hence, can only be seen for higher pH, [23][24][25] the corresponding process for DCB-SAMs peaks around À0.3 V vs SCE, that is, just before the hydrogen evolution reaction on gold. This is a clear indication for a lower bond strength between DCB and gold as compared to thiol-SAMs on gold.…”
Section: à2mentioning
confidence: 95%
“…It is shown that E p of the reductive desorption varies depending on the length of alkyl chain and the type of terminal group of SAMs. The longer the alkyl chain is, the more negative E p becomes, reflecting the stronger van der Waals attractive interaction among alkyl chains (Schilardi et al 2006). E p is also dependent on the terminal groups; E p of the reductive desorption of COOH(CH 2 ) n SH is more positive than that of CH 3 (CH 2 ) n SH.…”
Section: Reductive Desorption Of Sams On the Cathodementioning
confidence: 97%
“…However, no study has yet demonstrated that SAM desorption can be practically useful as reusable and reconfigurable biosensors, especially in microfluidic systems. This is because (1) when reductive potential is applied to the SAM-coated electrode, the opposite electrode suffers from corrosion (Santini et al 2000;Lukaszewski et al 2006) and (2) hydrogen evolution reaction (HER) occurs at a similar potential to the potential of the SAM desorption (Schilardi et al 2006). It is difficult to remove hydrogen bubbles by low flow rate of solution; typically several 10's of ll/min is used in microfluidic devices.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Patterned SAMs can also be used for the selective growth of metal nanostructures, 8 thin free-standing metal /magnetic films, 9 and for mold and replica fabrication. 10,11 Electrochemical deposition (ECD) is the simplest technique for depositing the metal being low-cost and compatible with complex patterning and manufacturing procedures. 8,12 To date a variety of SAM modified electrodes has been used including n-alkanethiol and ω-functionalised alkanethiol SAMs [13][14][15][16][17][18][19] as well as…”
Section: Introductionmentioning
confidence: 99%
“…18 Alternatively, if the Cu 2+ penetrates through the defect sites to the surface of the gold, the copper can grow from the surface leading to nanometer-sized columns and subsequently Ômushroom-shapedÕ growths. 11,31,46 In both cases the copper surface is exposed to air and it is expected that this will lead to the formation of a thin film of copper oxide. A third possibility is that the growth proceeds through penetration of Cu 2+ through the defects leading to a copper layer between the gold and the thiol.…”
mentioning
confidence: 99%